Kawasaki Disease Shock Syndrome in Japan and Comparison With Multisystem Inflammatory Syndrome in Children in European countries - Suzuki, Junko; Abe, Kota; Matsui, Takuya; Honda, Takafumi; Yasukawa, Kumi; Takanashi, Jun-ichi; Hamada, Hiromichi (Frontiers in Pediatrics, 2021)
Multisystem inflammatory syndrome in children (MIS-C) is a severe Kawasaki-like illness that was first linked to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in European countries in the spring of 2020 and has been suggested to have overlap with Kawasaki disease shock syndrome (KDSS). There are few reports of MIS-C from Asia. This observational study aimed to identify the clinical features in children presenting with KDSS in Japan over a 5-year period and to summarize similarities and differences between KDSS and MIS-C. We retrospectively collected data on patient characteristics, clinical signs and symptoms, treatment, and prognosis including coronary artery abnormalities (CAAs), which were compared with data of patients with KDSS worldwide and patients with MIS-C from a review. KDSS was identified in 6 (1.1%) of 552 patients with Kawasaki disease (KD) treated at a single institution in Japan between 2015 and 2020 (1 in 2020). In patients with KDSS in Japan or worldwide vs patients with MIS-C, KDSS was more likely to have a diagnosis of complete KD (100%, 70% vs 6.3%), a higher incidence of CAAs (50%, 65% vs 11%), and a greater requirement for vasoactive agonists (67%, 67% vs 43%) because of circulatory shock (100%, 50% vs 26%). Both KDSS and MIS-C had good prognosis (mortality 0%, 6.7% vs. 1.7%). Although KDSS in Japan and MIS-C show some overlap in clinical symptoms, they are unlikely to be the same disease entity. KDSS is more likely to have a cardiovascular phenotype with CAAs and requires treatment with cardiovascular agents.